2015
DOI: 10.1016/j.joto.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Improved hearing in noise using new signal processing algorithms with the Cochlear™ Nucleus® 6 sound processor

Abstract: ObjectiveTo demonstrate the performance benefit of the Automatic Scene Classifier (SCAN) algorithm available in the Nucleus® 6 (CP900 series) sound processor over the default processing algorithms of the previous generation Nucleus 5 (CP810) and Freedom® Hybrid™ sound processors.MethodsEighty-two cochlear implant recipients (40 Nucleus 5 processor users and 42 Freedom Hybrid processor users) listened to and repeated AzBio sentences in noise with their current processor and with the Nucleus 6 processor.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A specific aim of these studies was to examine the enhanced signal processing features of the N6 with existing Nucleus CI recipients. Some data in this paper were included in Gilden et al (2015). Because these studies used different protocols and procedures, they are reported separately.…”
Section: Study Purposementioning
confidence: 99%
“…A specific aim of these studies was to examine the enhanced signal processing features of the N6 with existing Nucleus CI recipients. Some data in this paper were included in Gilden et al (2015). Because these studies used different protocols and procedures, they are reported separately.…”
Section: Study Purposementioning
confidence: 99%
“…In addition, Digital circuitry, i.e., can be used in all types of medical devices and its design requires a set of filters that provides reasonable audiogram matching for the concerned type of hearing loss [35]. Some sound processors were developed to implement an automatic scene-classifying algorithm, which is an improvement over the previous generation of sound processing algorithms and is suitable for use by traditional cochlear implant and Hybrid L24 implant recipients [36].…”
Section: Types Of In-ear Medical Devicesmentioning
confidence: 99%